Development of normal phase HPLC based method for the determination of retinyl palmitate in fortified edible oils - Rakibul Hasan; Rokeya Begum; A.K. Obidul Huq; Nannur Rahman; Shamoli Akter; Shahinul Haque Khan; Faridul Islam (International Journal of Food Properties)
Fortification of edible oil with retinyl palmitate (vitamin A) is a significant advancement to fulfill the nutritional deficiency of major population. The growing interest in the enrichment of foods warrants a simple and accurate method to analyze fortified products. This study developed an easy and reliable strategy based on normal-phase HPLC analysis to determine the edible oil’s retinyl palmitate. We also validated the method according to the International Conference on Harmonization (ICH) guidelines. The analysis was performed with a DB silica column (250 cm × 4.6 mm; 5 μm), with a mobile phase composed of n-heptane and isopropyl alcohol at a ratio of 75:25 v/v and a flow rate of 1.0 ml/min. The detection was performed at a wavelength of 326 nm, and the retention time of vitamin A was around 8 min, with a total run time of 10 min. The calibration plot gave a linear relationship (R2 = 0.9998) over the concentration range of 3.93–63 μg/ml. The LOD and LOQ were 0.029 and 0.096 μg/ml, respectively. The accuracy of the proposed method was determined by recovery studies and was found with a mean recovery of >95%. RSD% of the determination of precision was <2%. The results of robustness and solutions stability studies were within acceptable limits. The proposed method showed excellent linearity, accuracy, precision, specificity, robustness, LOD, LOQ, and system suitability results within the acceptable criteria.